Feature Lines Modification Based on As-Stiff-As-Needed Surface Deformation. (November 2021) - Le Vaou, Youna; Léon, Jean-Claude; Hahmann, Stefanie; Masfrand, Stéphane; Mika, Matthieu
Abstract: Aesthetic surface mesh modification, guided by a deforming feature line, is still a challenging task. Whereas most existing surface deformation methods work well when the new surface is stretched or isometrically deformed, in case of areas subjected to compression, unwanted bulging may appear. This configuration typically appears when a designer slides a feature line along the input surface. In this paper, we present a new approach for feature line modification solving the surface bulging problem. We consider physically-based deformation methods applied to surface meshes and characterize configurations that produce compression loading from a mechanical standpoint. Then, the deformation area is decomposed into two sub-domains with a boundary modification of the one subjected to compression loading. Thus, during a subsequent deformation, this sub-domain no longer undergoes a compression loading but rather a traction loading, which ultimately prevents bulging. This transformation looks like a retraction of this surface area and a corresponding processing pipeline is set up. Our feature line modification method is intuitive to use and runs interactively, making it attractive to be used during design reviews in immersive environments. Industrial examples and comparisons with state-of-the-art physically-based deformation methods validate the proposed approach. Graphical abstract: Highlights: Interactive modification of feature lines using a physically-based approach. Analysis of physical phenomena to characterize the surface bulging effect when mimicking designers' modifications. Monitoring of physical phenomena through appropriate adaption of ASAN physically-based deformation method. Proposal of a deformation pipeline able to handle a wide diversity of feature lines configurations. Comparison with state-of-art deformation methods and application to industrial test cases.